2005
DOI: 10.1111/j.1463-5224.2005.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of posterior capsule disruption during phacoemulsification and associated postoperative complication rates in dogs: 244 eyes (1995–2002)

Abstract: The most significant complication of posterior capsule disruption during phacoemulsification is the inability to implant an intraocular lens. Intraocular lenses are more likely to be placed in eyes with intentional disruptions of the posterior capsule than those with accidental ruptures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Our data indicate that endophthalmitis following phacoemulsification cataract extraction is a rare event in dogs, occurring in three out of 368 at risk eyes in this study (0.82%). This is in general agreement with previous studies in dogs ( Johnstone & Ward, 2005 ; Sigle & Nasisse, 2006 ; Azoulay et al, 2013 ; Ledbetter, Spertus & Kurtzman, 2018 ) but higher than most studies in humans ( Liesegang, 2001 ; Ciulla, Starr & Masket, 2002 ; Kamalarajah et al, 2004 ; Li et al, 2004 ; Taban et al, 2005 ; Wejde et al, 2005 ; Ou & Ta, 2006 ; Rosha et al, 2006 ; Cao et al, 2013 ; Rudnisky, Wan & Weis, 2014 ). Furthermore, our data did not reveal that postoperative administration of systemic antibiotics protected against endophthalmitis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data indicate that endophthalmitis following phacoemulsification cataract extraction is a rare event in dogs, occurring in three out of 368 at risk eyes in this study (0.82%). This is in general agreement with previous studies in dogs ( Johnstone & Ward, 2005 ; Sigle & Nasisse, 2006 ; Azoulay et al, 2013 ; Ledbetter, Spertus & Kurtzman, 2018 ) but higher than most studies in humans ( Liesegang, 2001 ; Ciulla, Starr & Masket, 2002 ; Kamalarajah et al, 2004 ; Li et al, 2004 ; Taban et al, 2005 ; Wejde et al, 2005 ; Ou & Ta, 2006 ; Rosha et al, 2006 ; Cao et al, 2013 ; Rudnisky, Wan & Weis, 2014 ). Furthermore, our data did not reveal that postoperative administration of systemic antibiotics protected against endophthalmitis.…”
Section: Discussionsupporting
confidence: 93%
“…In humans the most common offending organisms are coagulase negative Staphylococci in acute cases ( i.e ., POD 2–7) and Propionibacterium acnes in more chronic cases ( Durand, 2013 ). The single culture-proven case in the present study was an Enterococcus , but the number of reported cases of post-phacoemulsification endophthalmitis in dogs is too limited to make any conclusions about predominance of any specific organism ( Johnstone & Ward, 2005 ; Sigle & Nasisse, 2006 ; Ledbetter, Spertus & Kurtzman, 2018 ). It has been shown that introduction of organisms into the eye during phacoemulsification is rather common in dogs and humans, yet development of endophthalmitis is rare ( Dickey, Thompson & Jay, 1991 ; Taylor et al, 1995 ; Tervo et al, 1999 ; Ledbetter, Millichamp & Dziezyc, 2004 ; Ledbetter, Spertus & Kurtzman, 2018 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Rhegmatogenous retinal detachment (RRD) develops when vitreous fluid enters the subretinal space between the neurosensory retina and the retinal pigment epithelium through a retinal tear 1–3 . RRD has many possible etiologies, including vitreous liquefaction, trauma, lens‐induced uveitis, lens luxation, lens surgery, vitreoretinal dysplasia, retinal cyst, and iatrogenic causes 1,2,4–14 . In dogs, RRD generally involves angles of greater than 90°, which is classified as giant RRD 3,4,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, phacoemulsification has been becoming a common surgical procedure for restoring vision in veterinary patients with cataract [9,12,19]. Postoperative pain can be caused by intraocular manipulations that irritate intraocular tissue and induce the subsequent inflammatory response in the veterinary patient undergoing ocular surgery including phacoemulsification [13].…”
mentioning
confidence: 99%